Impact of land requirements on electricity system decarbonisation pathways. (June 2019) - Palmer-Wilson, Kevin; Donald, James; Robertson, Bryson; Lyseng, Benjamin; Keller, Victor; Fowler, McKenzie; Wade, Cameron; Scholtysik, Sven; Wild, Peter; Rowe, Andrew
Abstract: Wind and solar power are predicted to dominate CO2 emission reductions in future electricity systems. Unlike spatially compact fossil fuels, harnessing renewable energy flows increases the land area impact of electricity production. This study quantifies the trade-offs between land area impacts, technology alternatives of decarbonisation pathways, and costs associated with reducing carbon emissions from electricity generation by ~ 90%. With its globally representative energy mix, the electricity system transition in Alberta, Canada is studied. OSeMOSYS optimizes generation capacity between 2015 and 2060 under various land impact scenarios. The wind and solar dominant reference scenario expands land area impacts tenfold. Under zero-land expansion constraints, costs increase by 11%, wind generation is eliminated, 15% and 55% of electricity is generated by rooftop solar and fossil fuels with carbon sequestration, respectively. Energy policy will need to designate increasing land areas for electricity production, or aid more compact low-carbon technology development. Highlights: Analyzes land area impact, technology pathways & costs of decarbonising electricity. Lowest-cost emission reductions of 90% expand land area impact tenfold (10×). Constraining land replaces wind by ground solar, then by rooftop solar & CCS. Constraining land increases total cost and reliance on CCS, reduces RE share. Policy must increase land for electricity production or support compact technology.